Kritik Sosial dalam Geguritan â€œDunga Munggah Pangkatâ€ Karya Budi Palopo - Qothrunnada, Nur Malisa; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of making this article is to find out the incompatibility of the work of Javanese literature on Geguritan Budi Palopo with the title "Dungo Mupload Rank" to be applied in daily life practice. This research based on the theory of the sociology of literature uses qualitative research, which is in line with the opinion (Ratna, 2013: 47) in (Autoridad Nacional del Servicio Civil, 2021) that the sociology of literature focuses on social signs that have to do with society as is the general characteristic of qualitative research. . Based on the sociological theory of literature, this research is descriptive in nature, because it explains clearly what is the content of this geguritan text, as the author wants to present to the reader. In making this article using the type/approach of research in the form of library research or library research. Literature study is a study that is used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories, etc. Library research or library search, namely research carried out through data collection or scientific writing aimed at the object of research or data. In accordance with the title of this geguritan, the poet shows a way so that his prayers or hopes for his promotion can be fulfilled. The first stanza describes how to deal with the ruler so that things run smoothly, namely by fawning. People who have a desire to increase in rank and rank are advised to be able to sort out and immediately humble themselves before the ruler, lick the ruler's feet, and make the authority of the ruler continue to grow.